Patient colon and rectal operative outcomes when treated with immune checkpoint inhibitors. Issue 9 (September 2021) - Calini, Giacomo; Abd El Aziz, Mohamed A.; Abdalla, Solafah; Saeed, Hamedelneel A.; Lovely, Jenna K.; D'Angelo, Anne-Lise D.; Behm, Kevin T.; Colibaseanu, Dorin T.; Mathis, Kellie L.; Larson, David W.
Abstract: There is limited data about the safety of colorectal surgery after immune checkpoint inhibitors (ICI). We aimed to share our experience about postoperative outcomes of colorectal surgery for patients treated with ICI. Overall, 31 patients were identified, 22 (71%) underwent elective and nine (29%) underwent emergent/urgent surgery. The 30-day Clavien Dindo class ≥ III complication rates were 27.3% (n = 6) for elective and 55.5% (n = 5) for emergent/urgent cases. Four patients underwent emergency surgery for immune-related colonic perforation and developed postoperative septic shock; two died. Considering patients' comorbidities, cancer stage, and surgical complexity, elective colorectal surgery after ICI seems relatively safe. However, emergent/urgent colorectal surgery was associated with high postoperative morbidity. Indeed, colonic perforation in the setting of ICI treatment has a significant risk of postoperative mortality. Therefore, for patients on ICI with any acute abdominal symptoms, surgical consult should be involved, and colon perforation should be ruled out.